Composite catalyst as well as preparation method and application thereof

By using the composite catalyst of derivative cobalt and g-C3N4, the problems of cumbersome and high cost of olefin hydroformylation reaction steps in the prior art are solved, and the reaction between olefins and synthesis gas is realized in one-step alcohol production, which improves product selectivity and the cycling capacity of the catalyst, which is suitable for industrial applications.

CN119613224APending Publication Date: 2025-03-14NINGXIA UNIVERSITY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311155408.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-08
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

In the prior art, the hydroformylation reaction of olefins usually requires two steps, the process is complicated and costly, and homogeneous catalysts have problems such as difficulty in separation, high ligand toxicity, and easy loss of active components in industrial applications.

Method used

Cobalt oxide with a specific morphology is prepared by hydrothermal method using a composite catalyst of derivatized cobalt and g-C3N4. Combined with electron effects, the formation and activation of cobalt active centers are promoted, and the reaction between olefins and synthesis gas is achieved in one-step alcohol production.

Benefits of technology

The reaction of one-step alcohol production is realized, which improves the selectivity of high-carbon linear alcohols, reduces the reaction temperature and pressure, and has good repetition and circulation ability of the catalyst, which is suitable for industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention relates to a composite catalyst and a preparation method thereof. The composite catalyst can be used for promoting long-chain alpha-olefin and a synthesis gas raw material to be subjected to continuous hydroformylation-hydrogenation reaction in one step to obtain a high-carbon alcohol product. Derived cobalt and graphite-phase carbon nitride in different proportions are compounded, the electronic effect is regulated and controlled, a high-dispersion and high-activity catalytic center is formed, and the composition of a product is effectively changed. The scheme provided by the invention has the advantages of simple preparation, controllable product, high alcohol selectivity and the like, and has a large-scale application and popularization prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of hydroformylation reaction product regulation, and specifically relates to a heterojunction composite catalyst and a preparation method thereof and an application of catalyzing olefins and synthesis gas to produce alcohol in one step. Background Art

[0002] Olefin hydroformylation is an important chemical industry processing reaction. The aldehyde products of catalytic olefin hydroformylation reactions are widely used in plasticizers, fragrances, gasoline additives, etc. High-carbon alcohols have important uses in the field of gasoline additives. Traditional synthesis and preparation use olefin hydroformylation (or carbonyl synthesis). Olefins are first hydroformylated to generate aldehydes, and then the aldehydes are further hydrogenated to generate the corresponding alcohols. Usually, the process is cumbersome through two steps, especially when expensive metal rhodium catalysts are used, and the process cost is too high. The one-step preparation of alcohols by olefin hydroformylation reaction with continuous reduction of cobalt-based catalysts is simple, with high selectivity of alcohol products and low overall cost, which can solve the above problems well. However, hydroformylation reactions involving cobalt-based catalysts often require higher reaction temperatures and reaction pressures. Researchers have tried to introduce strategies of organic phosphine ligands or additives to improve reaction activity and chemical / regioselectivity of products, and reduce reaction temperature and pressure. Although it shows certain advantages, there are also some problems. At present, Beller et al. in Germany have made certain progress in the direct preparation of alcohols by homogeneous catalytic olefin reduction hydroformylation, but the process is not yet mature. For example, the industrial production of isononyl alcohol mainly uses the cobalt catalyst developed by ExxonMobil. Under high pressure, octene is reacted with synthesis gas, and the crude aldehyde product is separated and further hydrogenated to obtain isononyl alcohol (Qilu Petrochemical, 2010, 38(4): 341-345). Unfortunately, the reaction is carried out under high pressure and in multiple steps. The prior art also reports the production of butyl octanol by a multi-step method: specifically, propylene is used as the raw material, butyraldehyde is produced by hydroformylation, and butyraldehyde is further hydrogenated to obtain butanol; butyraldehyde is condensed and dehydrated to obtain 2-ethylhexenal, which is further hydrogenated to obtain octanol (Chemical Management, 2013(14): 83). In addition, the multi-step reaction process is accompanied by the production of a high amount of alkanes, which makes the economic benefits of the device low. In the process of developing and expanding the catalytic system, the technical difficulties of homogeneous catalysis are also exposed, including: the difficulty in separating the catalyst and the product after the reaction, the high toxicity and poor stability of the ligand, the easy loss of the active components of the catalyst and the poor recycling capacity, and the high cost, all of which restrict the industrial application of homogeneous catalysis. If there can be breakthroughs in heterogeneous catalysis, especially in reducing or eliminating the use of ligands, anchoring active metal components, and improving catalytic cycle capabilities, it will accelerate the industrialization of the improved process.

[0003] The study found that cobalt oxide with a specific morphology obtained by hydrothermal method can catalyze 1-octene to produce nonanol through the reduction hydroformylation reaction process (Catal. Today, 2018, 309:147-152), but the catalyst dosage, reaction temperature, reaction time and other conditions significantly affect the conversion rate and selectivity, in other words, the repeatability is low. The addition of gold nanoparticles and alkali metal additives can improve the catalytic performance of cobalt oxide (Appl. Catal. A-Gen, 2020, 602: 117735), but it still takes a long reaction time to obtain alcohol products. CN115282968A discloses a transition metal-doped cobalt catalyst, and Fe-Cu doping can promote the performance of cobalt active centers; secondly, the study found that cobalt oxide catalysts with different exposed crystal faces have different phase evolution behaviors during the reaction, which significantly affects the product composition (Fuel, 2020, 269: 117397). gC 3 N 4 It has good photothermal, physical and chemical stability and is used as an oxidation photocatalyst in the low-valence band position, providing a new path for finding materials that match its band structure and constructing Z-type heterojunction photocatalysts (J. Alloys Compd., 2022, 890: 16178). The composite gC proposed by Zhou et al. 3 N 4 A stable 3D / 2D interface was formed, electron transfer occurred, and the photocatalytic water splitting reaction process showed a promoted redox performance; however, agglomeration occurred, affecting the hydrogen production rate and effect. Summary of the invention

[0004] In view of the advantages and disadvantages of the above research progress, the inventor aims to find a way to solve the problem of using a single material as a catalyst for two-step alcohol production, and adopts a method to control and form matching materials, which are applied to the one-step alcohol production reaction in the field of hydroformylation. This method has obvious advantages, such as simple preparation steps, good repeatability, effective regulation of product composition, stable active metals without loss, favorable generation of active species, and easy catalyst recovery, which has obvious advantages in industrial application.

[0005] The invention is creative: using gC 3 N 4 The special physical and chemical properties of the cobalt derivative gC are matched to effectively promote the one-step alcohol production capability of olefins and synthesis gas through continuous hydroformylation-hydrogenation reaction. 3 N 4 The composite catalyst, when used in the synthesis of high-carbon alcohols, produces a strong electronic effect, significantly improves the product composition, and increases the selectivity of high-carbon straight-chain alcohols. The derived cobalt is in situ reduced to the cobalt catalytic active center during the alcohol production reaction, without the need for additional energy input or pre-reduction procedures. 3 N4 The dispersion of cobalt active sites is improved; the concentration of oxygen vacancies formed by the derived cobalt is increased, CO adsorption activation is promoted, and the reduction of the derived cobalt to elemental cobalt is promoted through electronic effects, thereby improving the catalytic activity.

[0006] The beneficial effects of the present invention are as follows: the catalyst precursor is a derivative cobalt having a regular dodecahedral crystal structure (attached Figure 1-2 Description); Derived cobalt and gC 3 N 4 The composite not only improves the utilization rate of active cobalt species, but also increases the concentration of oxygen vacancies formed by the derived cobalt oxide, promoting the adsorption and activation of CO; and increases the surface electron density of cobalt (attached Figure 3 It is beneficial to the formation of cobalt species of the cobalt-derived active component and improves the activity of catalyzing olefins to alcohols in one step.

[0007] The catalyst of the present invention is described as nCo 3 O 4 -gC 3 N 4 ; Through self-derived cobalt and gC 3 N 4 Prepared by ethanol-assisted mixing and roasting; the homemade derived cobalt Co 3 O 4 It has a regular dodecahedral structure, gC 3 N 4 It has a lamellar structure.

[0008] The application scheme of the catalyst of the present invention in the continuous hydroformylation-hydrogenation one-step preparation of higher carbon alcohols is as follows: the reaction raw materials olefins include C 6 and C 6 One of the above linear α-olefins or internal olefins, preferably C 8 and C 8 The above linear α-olefins, the reaction solvent is tetrahydrofuran, 1,4-dioxane, N-methylpyrrolidone, N, N-dimethylformamide, dimethyl sulfoxide, acetonitrile, n-hexane, benzene, toluene, xylene, preferably tetrahydrofuran, synthesis gas (CO / H 2 ) volume ratio is 1 to 3, preferably CO / H 2 The volume ratio is 1, the mass ratio of catalyst to olefin is 1-20%, preferably 8-12%, the reaction temperature is 150-170 °C; the reaction pressure is 5-8 MPa, and the reaction time is 4-12 h, preferably 4-8 h. 3 O 4 With gC 3 N 4 The mass ratio is n, and the value of n is in the range of 0.05 to 0.2; the specific surface area of ​​the derived cobalt is ≥ 60 m 2 / g; composite catalyst specific surface area ≥10 m2 / g, and the pore size ranges from 2 to 50 nm.

[0009] The preparation method of the catalyst is to derive cobalt from a precursor; prepare it by a solvothermal method using cobalt nitrate and 2-methylimidazole; and calcine at 350 °C to obtain polyhedral derivatized cobalt. Melamine is calcined at 500 °C for 4 h, naturally cooled and then ground to obtain gC 3 N 4 . The derived cobalt and gC 3 N 4 Stir and mix to form a mixed ethanol solution to derive cobalt and gC 3 N 4 The mass ratio was 0.05-0.2. The ethanol solvent was removed by a rotary evaporator, and the resulting powder was collected and calcined at 300 °C in an air atmosphere for 1 h to obtain the target catalyst.

[0010] The catalyst can also be used to produce aldehyde products. The reaction conditions are similar to those of alcohol production: the raw material is straight-chain α-olefin, the volume ratio of synthesis gas is CO / H 2 is 1, the mass ratio of catalyst to raw material olefin is 8-12%, the reaction temperature is 110-130 °C, the reaction pressure is 5-8 MPa, and the reaction time is 4-10 h. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 These are SEM images of the catalysts prepared in Examples 1 and 2. Figure 2 XRD patterns of the catalysts prepared in Examples 1 and 2. Figure 3 XPS graphs of the catalysts prepared in Examples 1, 2 and 4. Implementation

[0012] The present invention is described in detail below by way of examples. It is necessary to point out that the following examples are only used to further illustrate the present invention and cannot be construed as limiting the scope of protection of the present invention. Without departing from the spirit and substance of the present invention, modifications or substitutions made to the methods, steps or conditions of the present invention all fall within the scope of the present invention.

[0013] Example 1 Add 3.15 g Co(NO 3 ) 2 6H 2 O and 0.9 g 2-methylimidazole were dissolved in 150 mL N, N-dimethylformamide, stirred for 30 min, and reacted at 170 °C for 48 h. Centrifugation, separation, washing, and drying at 65 °C for 12 h gave the precursor. The precursor was reacted with Co(NO 3 ) 2 6H 2O was dissolved in 50 mL of anhydrous ethanol at a mass ratio of 1:2 and stirred for 1 h. Centrifuged, washed, dried, and calcined at 350 °C (5 °C / min) for 2 h to obtain the derived cobalt.

[0014] Catalytic activity evaluation of nonanol synthesis: the mass ratio of catalyst to raw material 1-octene was 8.4%, the amount of catalyst was 0.1445 g, the amount of 1-octene was 1.68 g, the amount of solvent tetrahydrofuran was 10.65 g, and the volume ratio of synthesis gas was CO / H 2 The reaction temperature was 150 °C, the reaction pressure was 7 MPa, the stirring speed was 700 rpm, and the reaction time was 8 h. The reaction results are shown in Table 1.

[0015] Example 2 The preparation method of the derived cobalt is the same as that in Example 1. Melamine was calcined at 500 °C for 4 h, naturally cooled and then ground to obtain gC 3 N 4 . Derivative Cobalt and gC 3 N 4 The mass ratio was 0.05, dissolved in 20 mL ethanol, stirred at room temperature for 4 h, and the ethanol solvent was removed by a rotary evaporator. The resulting powder was collected and calcined at 300 °C in air atmosphere for 1 h to obtain 0.05Co 3 O 4 -gC 3 N 4 The activity evaluation of the composite catalyst was the same as in Example 1, and the reaction results are shown in Table 1.

[0016] Example 3 Derivative Cobalt and gC 3 N 4 The preparation method is the same as in Example 2. Derivatized cobalt and gC 3 N 4 The mass ratio was 0.1, dissolved in 20 mL of ethanol, stirred at room temperature for 4 h, and the ethanol solvent was removed by a rotary evaporator. The resulting powder was collected and calcined at 300 °C in air atmosphere for 1 h to obtain 0.1Co 3 O 4 -gC 3 N 4 The activity evaluation of the composite catalyst was the same as in Example 1, and the reaction results are shown in Table 1.

[0017] Example 4 Derivative Cobalt and gC 3 N 4 The preparation method is the same as in Example 2. Derivatized cobalt and gC 3 N 4The mass ratio was 0.2, dissolved in 20 mL of ethanol, stirred at room temperature for 4 h, and the ethanol solvent was removed by a rotary evaporator. The resulting powder was collected and calcined at 300 °C in air atmosphere for 1 h to obtain 0.2Co 3 O 4 -gC 3 N 4 The activity evaluation of the composite catalyst was the same as in Example 1, and the reaction results are shown in Table 1.

[0018] Table 1 Catalytic activity of 1-octene and synthesis gas to produce nonanol Example catalyst Conversion rate / % Nonanol selectivity / % Nonanal selectivity / % Alcohol / aldehyde 1 <![CDATA[Co 3 THE 4 ]]> 90.0 1.6 24.6 0.06 2 <![CDATA[0.05Co 3 O 4 -g-C 3 N 4 ]]> 99.9 77.8 1.1 70.7 3 <![CDATA[0.1Co 3 O 4 -g-C 3 N 4 ]]> 99.9 77.0 1.7 45.3 4 <![CDATA[0.2Co 3 O 4 -g-C 3 N 4 ]]> 99.8 9.7 68.7 0.2 Table 1 above shows that: Co 3 O 4 and composite Co 3 O 4 -gC 3 N 4 The catalysts all showed high feedstock conversion, especially the composite Co 3 O 4 -gC 3 N 4 The catalyst significantly changed the product composition.

[0019] Example 5 The catalyst of Example 2 was used, the activity evaluation was based on that of Example 1, the reaction time was 4 h, and the reaction results were shown in Table 2.

[0020] Example 6 The catalyst of Example 2 was used, and the activity evaluation was performed according to Example 1. The reaction time was 6 h, and the reaction results were shown in Table 2.

[0021] Example 7 The catalyst of Example 2 was used, and the activity evaluation was performed according to Example 1. The reaction time was 8 h, and the reaction results were shown in Table 2.

[0022] Example 8 The catalyst of Example 2 was used, and the activity evaluation was performed according to Example 1. The reaction time was 10 h, and the reaction results were shown in Table 2.

[0023] Example 9 The catalyst of Example 2 was used, and the activity evaluation was performed according to Example 1. The reaction time was 12 h, and the reaction results were shown in Table 2.

[0024] Table 2 Alcohol production activity of catalysts at different reaction times Example Reaction time / h Reaction temperature / °C Reaction pressure / MPa Conversion rate / % Nonanol selectivity / % Nonanal selectivity / % 5 4 150 7 99.8 28.9 63.1 6 6 150 7 99.6 40.4 49.9 7 8 150 7 99.9 77.8 1.1 8 10 150 7 99.9 48.1 15.2 9 12 150 7 99.9 13.5 51 Example

[0025] The catalyst of Example 2 was used, the activity evaluation was based on that of Example 1, the reaction temperature was 110 °C, and the reaction results are shown in Table 3.

[0026] Embodiment 11 The catalyst of Example 2 was used, the activity evaluation was based on that of Example 1, the reaction temperature was 130 °C, and the reaction results are shown in Table 3.

[0027] Example 12 The catalyst of Example 2 was used, the activity evaluation was based on that of Example 1, the reaction temperature was 150 °C, and the reaction results are shown in Table 3.

[0028] Embodiment 13 The catalyst of Example 2 was used, the activity evaluation was based on that of Example 1, the reaction temperature was 170 °C, and the reaction results are shown in Table 3.

[0029] Table 3 Alcohol production activity of catalysts at different reaction temperatures Example Reaction time / h Reaction temperature / °C Reaction pressure / MPa Conversion rate / % Nonanol selectivity / % Nonanal selectivity / % 10 8 110 7 99.7 3.8 90.3 11 8 130 7 99.6 5.8 81.8 12 8 150 7 99.9 77.8 1.1 13 8 170 7 99.8 63.2 2.4 The above Table 1-3 shows that: nCo 3 O 4 -gC 3 N 4 The composite catalyst showed high one-step alcohol production activity. Using 1-octene as the reaction material, the reaction was carried out at 150 °C and 7 MPa for 8 h. 3 O 4 -gC 3 N 4 Catalytic continuous hydroformylation-hydrogenation reaction, nonanol selectivity reached 77.8%. 110 °C, 7 MPa, 8 h, 0.05Co 3 O 4 -gC 3 N 4 The target reaction was catalyzed with a nonanal selectivity of 90.3%.

[0030] Embodiment 14 The catalyst of Example 2 was used, the activity evaluation was performed with reference to Example 1, the reaction raw material was 1-hexene, and the reaction results were shown in Table 4.

[0031] Embodiment 15 The catalyst of Example 2 was used, the activity evaluation was performed according to Example 1, the reaction raw material was 1-dodecene, and the reaction results were shown in Table 4.

[0032] Table 4 Reactivity of linear α-olefins with different carbon numbers to alcohols Figure 1 Scanning electron microscope (SEM) images of the catalysts prepared for Examples 1 and 2. 3 N 4 Preparation was successful.

[0033] Figure 2X-ray diffraction (XRD) spectra of the catalysts prepared in Examples 1 and 2. 3 N 4 The reunion was successful.

[0034] Figure 3 X-ray photoelectron spectroscopy (XPS) diagrams of the catalysts prepared in Examples 1, 2 and 4. 3 N 4 The electronic effect between them.

Claims

1. An application of a composite catalyst, characterized in that The composite catalyst is used for preparing alcohol in one step through continuous hydroformylation-hydrogenation reaction of olefins; the raw material olefin is one of linear terminal olefins or internal olefins, the reaction solvent is one of tetrahydrofuran, 1, 4-dioxane, methyl pyrrolidone, N, N-dimethylformamide, dimethyl sulfoxide, acetonitrile, n-hexane, benzene, toluene and xylene, the raw material synthesis gas (CO / H2) gas volume ratio is 1-3, the mass ratio of the catalyst to the raw material olefin is 1-20%, the reaction temperature is 110-170°C; the reaction pressure is 5-8 MPa, and the reaction time is 3-12 h; the catalyst is composed of a composite of derived cobalt Co3O4 and graphite phase carbon nitride g-C3N4, the derived cobalt Co3O4 presents a regular dodecahedral polyhedral crystal structure; the graphite phase carbon nitride g-C3N4 presents a lamellar crystal structure.

2. A method for preparing a composite catalyst as claimed in claim 1, comprising the steps of: (1) dissolving a cobalt salt and 2-methylimidazole in N, N-dimethylformamide, stirring, reacting at 170 °C for 48 h, centrifuging, separating, washing and drying; dissolving the product powder and cobalt nitrate in ethanol at a mass ratio of 1:2, stirring, centrifuging, washing, drying and calcining at 350 °C to obtain a derivative cobalt; (2) calcining melamine at 500 °C for 4 h, cooling and grinding to obtain g-C3N4; (3) weighing and mixing the derivative cobalt and carbon nitride at a certain mass ratio n, adding ethanol dropwise, stirring at 60 °C for 4 h, and calcining at 300 °C for 1 h to obtain the composite catalyst.

3. The use of the catalyst according to claim 1, characterized in that: The reaction raw materials include C6 and above straight-chain α-olefins, and the target product is C7 and above alcohols.

4. The method for preparing the catalyst according to claim 2, characterized in that: The mass ratio of Co3O4 to g-C3N4 is n, and the value of n is in the range of 0.05 to 0.

2.

5. The method for preparing the catalyst according to claim 2, characterized in that: The specific surface area of ​​the derived cobalt obtained by step-by-step method is ≥ 60 m 2 / g; composite catalyst specific surface area ≥10 m 2 / g, and the pore size of the composite catalyst is in the range of 2 to 50 nm.

6. The method for preparing the catalyst according to claim 2, characterized in that: The derivatized cobalt and carbon nitride were stirred and mixed with ethanol, and then the ethanol solvent was removed by rotary evaporation.

Citation Information

Patent Citations

  • Metal-doped self-assembled catalyst

    CN115282968A